Prostaglandin Synthesis in Aorta and Platelets of Fawn-Hooded Rats with Platelet Storage Pool Disease and Its Response to Cholesterol Feeding - Wey, H; Gallon, L; Subbiah, M T R (Thrombosis and Haemostasis, 1982)
Fawn-hooded (FH) rats possess a hereditary bleeding diathesis and platelet function defect, which is presumably the result of a storage pool deficiency. In this study, we have investigated the prostaglandin synthesis capacity of platelets and aorta from FH rats as compared to Sprague Dawley (SD) rats, after 2 months on a normal or 1% cholesterol diet. No difference was found in thromboxane B2 (TXB2) production by platelets of FH as compared to SD rats. Cholesterol-feeding resulted in an increased TXB2 production by SD platelets, but not FH platelets. FH rat aorta was found to convert significantly less arachidonic acid (AA) to 6-keto-prostaglandin-F1α (PGF1α) and cholesterol-feeding stimulated this reduced capacity. In contrast, cholesterolfeeding in the SD rat reduced aortic 6-keto-PGF1α production. Aggregation of platelet-rich plasma by AA was enhanced in the cholesterol-fed FH rat. This result suggests the possibility of an influence of platelet aggregability on aortic prostacyclin production.
Keywords: Hereditary platelet defect; Prostaglandins; Cholesterol diet; Platelet-endothelial interaction